Les infrastructures hydrauliques et la maîtrise de l’eau en Crau : de la production de l’abondance à la gestion de la rareté - Brice Auvet (Développement Durable et Territoires)
Hydraulic infrastructures are not a purely physical element taming the materiality of water. They are socially produced and their uses are transformed within a fabric of socio-spatial relations recomposed by this new materiality. This article articulates an history and sociology of science and technology with the analysis of power exercise to study concrete process of modernization for the redefinition of knowledge, infrastructures, roles and practices towards the mastership of water in Crau (South of France). We propose a local approach based on the hydraulic infrastructures built to generate abundance for France post-war reconstruction which are today in the center of water scarcity management apparatuses.